Energy management and control strategy of a grid‐connected PV/battery system. (18th April 2014) - Wu, Hongbin; Wang, Shuzhao; Zhao, Bo; Zhu, Chengzhi
Summary To reduce the negative influence on a power grid caused by the power fluctuations of photovoltaic (PV) generation systems, it is a good solution to stabilize the fluctuation with a battery. A common DC bus structure of a grid‐connected PV/battery system was built according to the characteristics of PV arrays and batteries. Based on models of the PV array and the battery, this paper studies the control strategies of the PV array, the battery and the grid‐connected inverter. We propose hysteresis energy management of the DC bus to avoid charging/discharging the battery frequently. To prevent the battery from switching back and forth between a working state and a stopping state, a nonlinear control function is used in the outer voltage control of the battery. The example system demonstrates the accuracy of the models and the control strategies and achieves constant grid‐connected transmitted power. This work provides a reference for a PV system that participates in power flow dispatching. Copyright © 2014 John Wiley & Sons, Ltd.